POS-UP: pembelajaran golongan kata menggunakan sajak (POS-UP : learning parts of speech using poems) / Sharifah Sheha Syed Aziz Baftim, Muhamad Izzat Rahim and Dzeelfa Zainal Abidin - Syed Aziz Baftim, Sharifah Sheha; Rahim, Muhamad Izzat; Zainal Abidin, Dzeelfa (Universiti Teknologi MARA, 2020)
Many language learners face difficulties in applying and using the parts of speech in a given situation. It has become a challenge for teachers to navigate a grammar lesson in a creative way that can help learners to understand and apply the concepts most appropriately. Thus, POS-UP designed as a supplementary teaching tool to allow language learners to practice using the most suitable parts of speech in a sentence. Targeted at English language learners, POS-UP is a game which provides players with the opportunity to learn details of a lesson using poems written by local poets. In this game, language learners must complete a poem by using words with the correct parts of speech. In making sure that this game reaches its objectives and fulfils the needs of the students, a survey was carried out to find out the perceptions of English language learners towards POS-UP. The result shows that learners who play this game find it enjoyable and helpful in enhancing their understanding of parts of speech. It is hoped that POS-UP will be a useful supplementary teaching tool for teachers in the classroom. It is also expected that students will build an appreciation towards poems written by local poets.